Teaching sustainability within the context of everyday life: Steps toward achieving the Sustainable Development Goals through the EUSTEPs Module - Moreno Pires, Sara; Mapar, Mahsa; Nicolau, Mariana; Patrizi, Nicoletta; Malandrakis, Georgios; Pulselli, Federico M.; Bacelar Nicolau, Paula; Caeiro, Sandra; Niccolucci, Valentina; Theodossiou, Nicolaos P.; Mancini, Maria Serena; Galli, Alessandro (Frontiers in Education, 2022)
In a world characterized by Ecological Overshoot, where humanity demands more from natural ecosystems than they can sustainably renew, education can nurture sustainability-minded citizens and future leaders to help accelerate the transition towards an era where our finite planet’s resources stand at the core of all decision-making. Despite the essential role of Higher Education Institutions (HEI) in contributing to a sustainable society, a holistic understanding of how to incorporate sustainability initiatives into HEI is still lacking. Given the critical role of HEI in societies and considering the number of students, educators, and staff they host every day, ensuring that sustainability is both taught and practiced on campuses becomes fundamental. To this end, a strategic partnership was created in 2019 to set up the ERASMUS+ project EUSTEPs - Enhancing Universities’ Sustainability Teaching and Practices through Ecological Footprint. Among the main outputs of the project is a teaching module for introducing the sustainability concept to students. This Module takes a 360-degree approach to teaching sustainability that is designed to help students grasp the extraordinary complexity of sustainability in an engaging and captivating manner. This paper thus aims to: 1) present the EUSTEPs Module, its pedagogical approach and structure, and the learning outcomes and competencies students are expected to gain; 2) review the outcomes of its first pilot teaching in four European HEI, and 3) shed light on how this Module contributes to the development of competences and pedagogical approaches for achieving the Sustainable Development Goals (SDGs). Our findings show that 90% of the students were ‘satisfied’ or ‘very satisfied’ with the Module, rating the Ecological Footprint as the most useful teaching tool among those included in the Module. In addition, they appreciated the interactive nature of the proposed teaching. Feedback obtained from students during the pilot teaching contributed to shaping the Module’s final structure and content. The Module – an important interactive sustainability pedagogical tool – is now ready for use with students in different disciplines, thus contributing to progress towards the UN 2030 Agenda, particularly SDG 4, SDG 11, SDG 12, and SDG 13.